Effectiveness of strategies for nutritional therapy for patients with type 2 diabetes and/or hypertension in primary care: Protocol of a systematic review of randomised controlled trials - Galendi, Julia Simões Corrêa [UNESP]; Leite, Renata Giacomini Occhiuto Ferreira [UNESP]; Mendes, Adriana Lúcia [UNESP]; Nunes-Nogueira, Vania Dos Santos [UNESP] (BMJ, 2019)
Introduction Despite the increasing number of drugs available and various guidelines on the management of type 2 diabetes mellitus (T2DM) and hypertension, an expressive number of patients continue with these diseases uncontrolled. Nutrition therapy (NT) plays a fundamental role in the prevention and management of these comorbidities, as well as in the prevention of complications related to them. The objective of this review is to evaluate the effectiveness of NT strategies in the management of patients with T2DM and/or hypertension in primary care. The selected strategies did not substitute pharmaceutical treatment but instead focused on preventing a sedentary lifestyle and stimulating healthy nutrition. Methods and analysis We will perform a systematic review according to Cochrane methodology of randomised controlled trials, wherein patients with T2DM and/or hypertension were allocated into one of the two groups: NT strategy, which may be of dietary quality or energy restriction, and conventional treatment. The primary outcomes will be glycaemic and blood pressure (BP) control, measured by final glycosylated hemoglobin (HbA1c) (%) and BP (mm Hg), respectively. Four general and adaptive search strategies have been created for the Embase, Medline, Latin American and Caribbean Health Sciences Literature (LILACS) and Cochrane Central Register of Controlled Trials (CENTRAL) electronic databases. Two reviewers will independently select eligible studies, assess the risk of bias and extract data from the included studies. Similar outcomes measured in at least two trials will be plotted in the meta-analysis using Review Manager V.5.3. The quality of evidence of the effect estimate of the intervention will be generated according to the Grading of Recommendations Assessment, Development, and Evaluation Working Group. Ethics and dissemination As no primary data collection will be undertaken, formal ethical assessment is not required. We plan to present the results of this systematic review in a peer-reviewed scientific journal, conferences and the popular press. PROSPERO registration number Our systematic review protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on 20 December 2018 (Registration number CRD42018118117).
Keywords: hypertension; meta-analysis; nutrition therapy; primary health care; systematic review; type 2 diabetes mellitus